AN ERROR ANALYSIS OF ACTION VERB USAGE IN NARRATIVE WRITING OF ELEVENTH GRADE STUDENTS OF SMKS IMMANUEL MEDAN - Marbun, Paulina; Rina Octavia Simarmata; Ernawati Tampubolon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A Thesis The ability to use correct grammar in narrative writing is essential for students to express ideas clearly. The purpose of this study was to identify and analyze errors in the use of action verbs based on the surface strategy taxonomy proposed by Dulay, Burt, and Krashen. This research used descriptive qualitative design. The subjects of this study were fourteen eleventh-grade students of SMKS Immanuel Medan, and the instruments were students’ narrative writing tests and interviews. The data analysis followed Ellis’s theory of error analysis which includes identifying, describing, explaining, and evaluating. The findings showed that there were three types of errors, namely 226 (96.58%) misformation errors, 7 (2.99%) addition errors, and 1 (0.43%) misordering error, while no omission errors were found. Based on these results, it can be concluded that misformation was the most dominant type of error made by students in using action verbs. It is suggested that teachers provide more explicit instruction and practice in verb usage, while future researchers may use this study as a reference for further analysis in different text types.